The influence of temperature on oxygen consumption rates of workers of two leaf cutting ants, Atta laevigata (F. Smith, 1858) and Atta sexdens rubropilosa (Forel, 1908) - Hebling Beraldo, Maria JoséAparecida [UNESP]; Mendes, Erasmo Garcia [UNESP] (Elsevier B.V., 1982)
1. 1. The oxygen consumption in workers of two simpatric leaf cutting ants, Atta laevigata and Atta sexdens rubropilosa was measured at different temperatures. 2. 2. In the temperature range between 5-35°C, with 5°C increments, the respiratory rates increased with temperature, but the R-T curves of both ants showed neither a marked drop at the low end nor a break at the high end; except between 30 and 35°C. 3. 3. The respiratory rates of A. s. rubropilosa were higher than those of A. laevigata and in the midrange of temperatures, the rates of A. laevigata increased faster than those of A. s. rubropilosa. 4. 4. Q10 values did not indicate regions of compensation for temperature in both ants, but suggested that adjustments may occur at high temperatures (25-35°C), as expected for tropical ants. 5. 5. Temperature variations did not alter significantly the slope of the curve relating oxygen consumption and body weight in both species. © 1982.